Studi Fenomenologi: Pengalaman Orang dengan HIV/AIDS (ODHA) yang Menjalani Terapi Antiretroviral - Nailiy Huzaimah; Iva Gamar Dian Pratiwi (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Antiretroviral (ARV) influences various side effects that cause discomfort both physical and psychosocial dimensions in people with HIV / AIDS (PLWHA). This study aims to explore and uncover the experiences of ODHA who are undergoing ARV therapy (ART) in Sumenep Regency. This research design was a qualitative phenomenological study. Data collection techniques used to interview and observation. Interviews were conducted with PLWH participants (n = 11), responsible people of HIV at the Community Health Center (CHC), and Public Health Office. Interview transcripts were thematically analyzed. The results of this study found 7 themes that describe the PLWH's experiences receiving ARV, those were comprehension of HIV / AIDS while the following ART, the feelings of knowing HIV positive, experiences of stigmatization and discrimination, the main supporter in undergoing ART, prior experience starting ART, experiences during the improvement of ART, and efforts to reduce drug side effects. The conclusion of this study was the PLWHs' experiences were revealed in various stories based on the underlying perspective. Each individual's experience contains information, expressions of feelings, and hopes that need to be the focus of the attention of health workers in assisting and providing care for PLHIV who are on ART. Suggestions for further research are quantitative research using objective and more measurable instruments on basic knowledge, opportunistic infections, the severity of ART's side effects, CD4 cell counts, viral load, and psychological, social, and spiritual well-being related to PLWH receiving ARV.